Comparison of Sleeve Lobectomy for Lung Cancer Using Mini-Thoracotomy and an Optimized Robot-Assisted Technique. (October 2021) - Shaolin, Tao; Yonggeng, Feng; Poming, Kang; Longyong, Mei; Cheng, Shen; Chunshu, Fang; Licheng, Wu; Qunyou, Tan; Bo, Deng
Objective: To evaluate the clinical significance of an optimized approach to improve surgical field visualization and simplify anastomosis techniques using robotic-assisted sleeve lobectomy for lung or bronchial carcinoma.Method: A total of 26 consecutive patients who underwent sleeve lobectomy between January 2017 and April 2020 were enrolled in the study. The cohort included 11 cases of robotic-assisted surgery (RAS group) and 15 cases of mini-thoracotomy (MT group). RAS was performed via an exclusive optimized approach utilizing the "3 to 4-6 to 8/9" four-port technique. Retrieved demographical and clinical data included operation time, anastomosis time, blood loss, chest drainage time and volume, postoperative pain scores, complications, white blood cell (WBC) levels, and duration of hospital stay and follow-up.Results: No cases of perioperative death were recorded. Compared to MT group, the RAS group had a similar anastomosis time (30.82  ±  6.08 vs 33.20  ±  7.73 min, respectively, p > 0.05) and shorter operation time (189.73  ±  36.41 vs 225.33  ±  38.19 min, respectively, p < 0.05). The RAS group had lower pain scores (4.23  ±  0.26 vs 4.91  ±  0.51, p < 0.05), lower levels of WBC (p < 0.05), and no anastomotic complications postoperatively. The RAS and MT groups demonstrated a successful bronchus reconstruction with low risk of angulation (1/11 vs 1/15, p > 0.05) and satisfactory disease-free survival (eight cases, 72.73% and 12 cases, 80%, respectively).Conclusion: The optimized approach to RA sleeve lobectomy is convenient and efficient and provides satisfactory clinical outcomes. Further study with a large sample size and evaluation of long-term survival are warranted.Key points: (i) we present a novel, convenient, and efficient approach for robotic-assisted sleeve lobectomy, ie, "3 to 4-6 to 8/9" four-port technique. The optimized approach for RA sleeve lobectomy is convenient and efficient and provides satisfactory clinical outcomes; (ii) details for the "3 to 4-6 to 8/9" four-port method: the assistant port was located at the fourth intercostal space. The 1-cm camera port was inserted at the sixth intercostal space in the posterior axillary line. The 0.5-cm da Vinci ports of the instrument arms were placed at the third intercostal space in the anterior axillary line and the eighth or ninth intercostal space in the posterior axillary line. The patient cart was inserted from the back of the patient's head and shoulders at 75° to the longitudinal line.